1998
DOI: 10.1080/01496399808545279
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Lead from Aqueous Solutions Using Rice Husk

Abstract: Rice husk, an agricultural waste, was studied as a potential scavenger of lead from various aqueous solutions. Physicochemical parameters such as selection of appropriate electrolyte, shaking time, and the concentrations of adsorbent and adsorbate were studied to optimize the conditions to be utilized on a commercial scale for the decontamination of effluents using a batch technique. Maximum adsorption was observed with 0.01 moldm" 3 acid solutions (HNO 3 , HC1, H 2 SO 4 and HC1O 4 ) using 1000 mg of adsorbent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
18
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 26 publications
9
18
0
Order By: Relevance
“…It is clear from results as shown in Figure 4 [13][14][15] . The sorption characteristics indicated that surface saturation was dependent on initial metal ion concentration.…”
Section: Effect Of Solution Concentrationmentioning
confidence: 57%
“…It is clear from results as shown in Figure 4 [13][14][15] . The sorption characteristics indicated that surface saturation was dependent on initial metal ion concentration.…”
Section: Effect Of Solution Concentrationmentioning
confidence: 57%
“…Agricultural wastes and by-products are good candidates in that they are low-cost, renewable sources with high carbon and volatile contents, low ash, and reasonable hardness. Examples of investigations utilizing agricultural biomass sources for activated carbon production in the recent two decades include: almond shells and peach stones [3]; olive stones and pulp [4][5][6]; apricot stones [7,8]; date pits [9]; apple pulp [10]; sugarcane bagasse [11]; rice husks [12]; and nutshells and fruit stones [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Effect of pH The increased adsorption at higher temperatures can be due to one or more of the following reasons. Acceleration of some originally slow step(s) 18 ; creation of some new activation sites on the adsorbent surface 18 and decrease in the size of the adsorbing species 19 . This could well occur due to progressive desolvation of the adsorbing ion as the solution temperature increases.…”
Section: Effect Of Temperaturementioning
confidence: 99%